Blinking Red : Crisis and Compromise in American Intelligence after 9/11 - Allen, Michael, 1972- (Book collections on Project MUSE., 2013)
"Blinking Red illuminates the complicated history of the bureaucratic efforts to reform America's national security after the intelligence failures of 9/11 and Iraq's missing weapons of mass destruction, explaining how the NSC and Congress shaped the U.S. response to the 9/11 attacks. Michael Allen asserts that the process of creating the DNI position and the NCTC is a case study in power politics and institutional reform. By bringing to light the legislative transactions and political wrangling during the reform of the intelligence community, Allen helps us understand why the effectiveness of these institutional changes is still in question."--Www.Amazon.com.